ANALISIS EFISIENSI PEMANFAATAN INFRASTRUKTUR TRANSPORTASI DARAT DI ASEAN-5 TAHUN 2015-2022 - Nuri Nur Azizah; Pratiwi Dwi Karjati; Gigih Pratomo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of land transport infrastructure plays a strategic role in enhancing regional connectivity, supporting public mobility, and driving economic growth across ASEAN nations. However, the availability of extensive infrastructure does not necessarily guarantee efficient utilization. This study aims to analyze the efficiency of land transport utilization in the ASEAN-5 countries—Brunei Darussalam, Indonesia, Malaysia, Singapore, and Thailand—during the 2015–2022 period. A quantitative approach was employed using the Data Envelopment Analysis (DEA) method, specifically the input-oriented Constant Returns to Scale (CRS) model. The input variables included total road length, total paved road length, and the number of motor vehicles, while the output variables comprised the total number of road-based commercial vehicles, urban population, and the transport sector's GDP. The results indicate that the efficiency levels of land transport infrastructure utilization among the ASEAN-5 countries varied throughout the 2015–2022 period. Singapore, Thailand, and Brunei most frequently reached the efficiency frontier, whereas Indonesia and Malaysia did not achieve an efficient state during the study period.